The simple past tense learnability in reading for eight-graders - Wisnuwardhani, Sitaresmi Imaniyati; Robiasih, RR.Hasti; Sukur, Silvester Goridus (Journal of English Language and Pedagogy, 2023)
The study aims to determine the simple past tense learnability in reading for eighth-grade students. This study uses qualitative research methods. Data were collected through observation, interviews, document studies, and questionnaires. The analysis used is the analysis of the Miles and Huberman models. Observations were made to see how students produce simple past tense sentences directly without the reading text. The reading comprehension test is used to see how students produce the simple past tense with reference to the reading. Student errors during observation and when doing tests are used to see the learnability. Interviews and questionnaires were used as supporting data from the reading comprehension test results and observation. Based on the results of data analysis, it can be concluded that simple past tense learnability in reading for eighth graders is low. This can be seen from the errors made by students. Based on the observation, students make overgeneralized, global, and local errors. Most students make global errors and misinformation through the reading comprehension test. Reading only helps a little in understanding the sentence structure of the simple past tense. Students tend to imitate the sentences in the reading. However, when students produce sentences independently, they need help correctly using the simple past tense sentence structure.